Relevansi Politik Kekuasaan Dan Kinerja Birokrasi Pasca Pemilihan Bupati Dan Wakil Bupati Aceh Barat Periode 2017-2022 Di Dinas Kesehatan - Chairullah Chairullah; Nurliah Nurdin; Dian Anggraeni (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2022)
This study focuses on the relationship between the Pilkada and the performance of the Aceh Barat Health Office. This study aims to analyze the relevance of power politics to the performance of the West Aceh Health Service bureaucracy that has not been optimal, and to find a solution so that the West Aceh Health Service bureaucracy is protected from the political impact of the Pilkada. The main theories used are Peter Merkl's theory of power politics (Budiardjo, 2007), Weber's bureaucratic neutrality (Miftah Thoha, 2014) and Sofian Effendi, 2018), and bureaucratic performance theory (Agus Dwiyanto. 2012). Bureaucracy must be impartial, which means it must be fair, objective, unbiased and not in favor of anyone. Mutations and promotions are indicated to be related to the Pilkada process in West Aceh which has affected the West Aceh Health Service so that performance in serving the public is disrupted. The politicization of power and the performance of the bureaucracy in Aceh Barat Regency was shown in the form of inappropriate promotions and mutations at the Aceh Barat Health Office. Some of them are: 1) promotion of functional dr in Puskesmas to become director of CND Hospital in 2018, 2) recruitment of Freelance Daily Workers (THL) for cleaning staff, administrative staff and health workers at CND Hospital, 3) transfer of Puskesmas midwives to the secretariat DPRK, 4) transfer of specialist doctors from CND Hospital to Puskesmas. The solution to prevent the politicization of power is by means of the DPRK exercising tighter control over the policies of the regent. For example, by creating a special committee and urging the regent to remove the incompetent director of the RSUD.